Analisis Pembuatan Asam Lemak Hidroksamat Dari Minyak Kelapa Melalui Metode Enzimatis - Muhsinun Muhsinun (JUPE : Jurnal Pendidikan Mandala, 2019)
Generally, fatty hydroxamic acids (FHA) are synthesized from basic ingredients containing fatty acids.Fatty acids can be obtained from coconut oil among several other sources. Coconut oil contains fatty acids with medium and long chains so it has enormous potential as a raw material for the synthesis of hydroxamic fatty acids. The purpose of this research is to synthesize FHA from coconut oil enzymatically and determine the amount of FHA products produced. The method used is the enzymatic method which includes several stages of work, namely the synthesis stage, the multiplication stage, and the purification stage. From the research results, the percentage obtained from the synthesis was around 48.58% of hydroxamic fatty acids from coconut oil after propagation using the synthesis conditions.The number of hydroxamic acid groups in 1 gram of dry hydroxamic fatty acid sample was 2.97 mmol. Thus, from the two results mentioned above, it was concluded that hydroxamic fatty acids can be synthesized from coconut oil